Konstruksi Masyarakat Menurut Mahatma Gandhi - Wisarja, Ketut; Sudarsana, I Ketut (Universitas Muhammadiyah Ponorogo, 2018)
The cotruction of society that Gandhi is trying to build is a manifestation of his religious or religious faith. Where each individual jointly runs his life activity in the life of society as a holy dharma of religion. As dharma then every individual must be able to defeat any potential greed in developing autonomization of individuality to realize mutual interests. The idealization of society that Gandhi aspires to is inseparable from the idealization of the perfection of human beings as the main core of society. The idealization of society for Gandhi is what the Indian community calls the ashram. Ashram has in common with ashrama terminology. Ashram is the ideal conception of community building as a model community. Such community prototypes contain a set of cultural roots that make up the ideological constructions of society. The cultural roots are established as living principles that must be obeyed by the ashram citizens. The estuary of all is the enforcement of the principle of brotherhood of mankind. The value of humanity that is the culmination and the key word for every form of devotion by upholding that all human beings are equal and brothers, should not be exaggerated or feel more than others. This principle of 'all brothers' is the moral principle in Gandhi idealized society. The implications of Gandhi's thought increasingly find a point of relevance to forming civil society in Indonesia.